3D gel-printing—An additive manufacturing method for producing complex shape parts. (5th July 2016) - Ren, Xiangyuan; Shao, Huiping; Lin, Tao; Zheng, Hang
Abstract: A new 3D printing process, 3D gel-printing (3DGP) based on methaerylate-2-hydroxy ethyl (HEMA) gelation system, was proposed in this paper, and as an example, 316L stainless steel gear was prepared by 3DGP. The rheological behavior of metal slurry, the surface roughness and strength of green sample and sintered sample were researched. The results show that the metal slurry with a 316L particle content of 62.5 vol% can be prepared with a HEMA-based gelation system, whose rheological behavior is fit for printing. Catalyst can accelerate the gelation so that complex shape of parts could be setting in time during printing. The green sample has a strength of 16.1 ± 2.2 MPa and a roughness of 3.5 ± 0.5 μm on top surface. The sintered sample has a homogeneous microstructure and no interface between the printed layers and lines was observed. The sintered sample has a roughness of 3.8 ± 0.9 μm on top surface and a tensile strength of 488 ± 15 MPa. Generally, 3DGP based on HEMA gelation system is a promising method for producing complex shape parts. Graphical abstract: Highlights: A new method of 3D gel-printing was developed by combining gelation and 3D printing. With optimizing the property of slurry, a stainless steel gear was fabricated as an example. The green sample has a bending strength of 16.1 MPa, surface roughness of 3.5 μm. The sintered sample has a surface roughness of 3.8 μm and tensile strength of 488 MPa.